COMPARACIÓN DEL EFECTO DE OCHO MODIFICACIONES DIETARIAS SOBRE LOS NIVELES DE LÍPIDOS SÉRICOS DE PACIENTES DISLIPIDEMICOS DE SANTA FE DE BOGOTA, 1996 (Universitas Scientiarum, 2013)
The aim of this study was to compare the effect of severa! dietary modifications on serum Iipids levels of dislipidemic patients from Santa Fe de Bogotá. 160 subject with serum cholesterol levels abo ve 200 mg/dl ortriglycerides abo ve 150 mg/dl were divided in 8 groups of20 patients, as follows: control group with the diet recommended by the International Lipid Infonnation Bureau (ILIB), rnodified-fat group, blackberry, citric fruits, oat or 1egurnes addition group, weight reduction diet group and sucrose exclusion group. Compared to control treatrnent, the addition of oat and legumes were more effective (p